2010
DOI: 10.1128/aac.01538-09
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fungicidal Activities of Echinocandins against Candida metapsilosis , C. orthopsilosis , and C. parapsilosis Evaluated by Time-Kill Studies

Abstract: Anidulafungin, micafungin, and caspofungin in vitro activities against Candida metapsilosis, C. orthopsilosis, and C. parapsilosis were evaluated by MICs and time-kill methods. All echinocandins showed lower MICs (mean MICs, 0.05 to 0.71 mg/liter) and the highest killing rates (؊0.06 to ؊0.05 CFU/ml/h) for C. metapsilosis and C. orthopsilosis rather than for C. parapsilosis (mean MICs, 0.59 to 1.68 mg/liter). Micafungin and anidulafungin killing rates were greater than those determined for caspofungin. None of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
32
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 16 publications
1
32
0
1
Order By: Relevance
“…In 2005, Tavanti et al (48) suggested that the C. parapsilosis complex could be replaced by 3 different closely related species named C. parapsilosis sensu stricto, C. orthopsilosis, and C. metapsilosis. These species may show differences in antifungal susceptibilities and virulence, and an increased interest in the study of their epidemiology has arisen in the last years (8,19,23,31,34,46,47,51,52). Interestingly, the incidence of C. orthopsilosis and C. metapsilosis infections may have increased since 2004 (31), with prevalence rates ranging from 2.3 to 9% and 0.9 to 6.9%, respectively, depending on the geographical area and clinical specimens analyzed.…”
mentioning
confidence: 99%
“…In 2005, Tavanti et al (48) suggested that the C. parapsilosis complex could be replaced by 3 different closely related species named C. parapsilosis sensu stricto, C. orthopsilosis, and C. metapsilosis. These species may show differences in antifungal susceptibilities and virulence, and an increased interest in the study of their epidemiology has arisen in the last years (8,19,23,31,34,46,47,51,52). Interestingly, the incidence of C. orthopsilosis and C. metapsilosis infections may have increased since 2004 (31), with prevalence rates ranging from 2.3 to 9% and 0.9 to 6.9%, respectively, depending on the geographical area and clinical specimens analyzed.…”
mentioning
confidence: 99%
“…They found C. parapsilosis most frequently in adult intensive care unit, surgery, and internal medicine departments, and in their study, most C. parapsilosis candidemias were observed in adults (4). Moreover, the new class of echinocandin broad-spectrum antifungals-although very active against C. albicans or C. glabrata-shows increased MICs against most clinical isolates of the C. parapsilosis group (15), with differences at the species level (3).…”
mentioning
confidence: 99%
“…Candida species are the cause of nosocomial sepsis, septic shock, and lethal disseminated infection in critically ill patients admitted to intensive care units (ICUs), rising over the past decade to the fourth most common pathogens causing nosocomial bloodstream infections in the United States (3). The increasing frequency rate of serious Candida hospital infections in intensive care patients has multifactorial causes, including increasing usage of intravascular catheters, broad-spectrum antibiotics, extensive surgery, and immunosuppression for neoplastic disease or allograft preservation (2,8).…”
mentioning
confidence: 99%
“…In 2005, Tavanti et al suggested that the 3 groups of C. parapsilosis should be replaced by 3 different related species named C. parapsilosis sensu stricto, C. orthopsilosis, and C. metapsilosis (25). Since then, an increased interest in studying the epidemiology has arisen based on the observed differences in antifungal susceptibilities and virulence among the three species (4,6,7,10,15,17,19,23,24,28,29). Differentiating among the three species of the C. parapsilosis sensu lato group cannot be achieved by phenotypic methods.…”
mentioning
confidence: 99%